Isolated Single-phase High Power Factor Rectifier Using Zeta Converter Operating in DCM With Non-Dissipative Snubber - Alan D. Callegaro; Denizar C. Martins; Ivo Barbi (Eletrônica de Potência)
This paper presents the study of a single-stage, single-phase, unity power factor converter, isolated by a high frequency transformer, based on a Zeta converter operating in discontinuous conduction mode (DCM). The main feature of the proposed converter is its ability to naturally emulate an apparent resistance to the ac input source, without current sensor or current controller. Circuit operation, theoretical analysis and design example are included in this paper, along with experimental results taken from a laboratory prototype rated at 400W, input voltage equal to 127 V, output voltage equal to 200 V, switching frequency of 25 kHz and efficiency of 92 %. In order to reduce the commutation losses and limit the peak voltage across the power semiconductors, a non- dissipative snubber has been included in the laboratory prototype. With the advent of new low losses power semiconductor technologies, such as SiC and GaN, power converters operating in DCM will become very attractive, due to their simplicity and robustness, even for high power applications. This is the main motivation of the study presented hereafter.